PENGARUH PEMBERIAN KOMPOS GULMA SIAM (Chromolaena odorata) TERHADAP POPULASI LALAT BUAH PADA TANAMAN CABAI - Eko Apriliyanto; Dewi Hastuti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2012)
ABSTRACTThis research aimed at knowing the potentials of composed siam weed (Chromolaena odorata) for enhancement of crops performance and its effect to fruitflies population’s to chili crops. The research was carried out at the experimental plantation of Agriculture Faculty, Gadjah Mada University, Banguntapan, Bantul, Yogyakarta from Oktober 2009 up to Maret 2010.This research used Randomize Complete Block Design used with 4 treatments, i.e., composed siam weed 40 ha-1 (G), dunk manure of cow 40 ha-1 (S), NPK (N) (Urea N 46% 40 kg/1000 m2, SP 36 20 kg/1000 m2, and KCL 20 kg/1000 m2), and without fertilizer as control (K) were 4 treatmens to repeated 6 time. Observation of arthropods population was taken with interval of 1 week. Crops samples observed were consisted of 2 plants per treatment. Crops performances observed were fruit number, fresh weight and dry weight of fruit, fresh weight and dry weight of crops. Totals N-leaf was analyzed on generative phases of the crops.Composed siam weed can not increased damage of herbivores if compared with other treatment, it’s indicated that highest of weigh of fruits and weight of crops. The result of research indicated that composed siam weed if compared with NPK and dunk manureof cow, that composed siam weed can not increased frutflies population. It suggest fruitflies prefer nutrition on fruit to secondary compound in chili crop.Key words: fruitflies, population, siam weed, chili.